Marginal abatement costs for greenhouse gas emissions in the United States using an energy systems approach - Michael Blackhurst; Aranya Venkatesh; Aditya Sinha; Katherine Jordan; Nicholas Z Muller; Cameron Wade; Jeremiah X Johnson; Paulina Jaramillo (Environmental Research: Energy)
Deep decarbonization requires fundamental changes in meeting energy service demands, with some efforts increasing overall costs. Examining abatement measures in isolation, however, fails to capture their interactive effects within the energy system. Here we show the abatement costs of decarbonization in the United States using an energy system optimization model to capture technological interactions, multi-decadal path dependence, and endogenous end-use technology selection. Energy-system-wide net-zero CO _2 -eq emissions are achieved in 2050 at a cost under $400 per tonne CO _2 -eq, led by emissions reductions in power generation, end-use electrification of ground transportation, space heating, and some industrial applications. Differences in mitigation costs and CO _2 geological storage potential lead to regional heterogeneities in mitigation rates and residual emissions. The marginal abatement cost curves show that additional decarbonization comes at higher incremental costs, this cost penalty decreases over time, and substantially greater abatement occurs in future time periods at the same abatement cost.